2017
DOI: 10.1038/aps.2017.13
|View full text |Cite
|
Sign up to set email alerts
|

Wenshen Zhuanggu formula effectively suppresses breast cancer bone metastases in a mouse Xenograft model

Abstract: Wenshen Zhuanggu formula (WSZG) is a traditional Chinese medicine used as an adjuvant for the prevention of bone metastases in breast cancer patients. In this study we investigated the efficacy of WSZG in preventing bone metastases and the potential mechanisms in a mouse xenograft model of breast cancer bone metastases. This model was established by injection of human MDA-MB-231BO-Luc breast cancer cells alone or a mixture of the cancer cells with bone marrow-derived mesenchymal stem cells (BMSCs) into left ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Recently, studies on the anticancer effects of natural products have been conducted, and interest in natural product-derived medicines is increasing [29][30][31][32]. According to our previous report, Angelica gigas (Ag), Zingiber officinale Roscoe (Zo), and Aconitum carmichaeli (Ac) showed anticancer effects in the cell lines of several cancers, including brain, breast, prostate, colorectal, skin, and pancreatic cancer [33][34][35][36][37][38]. Furthermore, it is known that natural treatments for various inflammatory diseases and obesity have neuroprotective effects [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies on the anticancer effects of natural products have been conducted, and interest in natural product-derived medicines is increasing [29][30][31][32]. According to our previous report, Angelica gigas (Ag), Zingiber officinale Roscoe (Zo), and Aconitum carmichaeli (Ac) showed anticancer effects in the cell lines of several cancers, including brain, breast, prostate, colorectal, skin, and pancreatic cancer [33][34][35][36][37][38]. Furthermore, it is known that natural treatments for various inflammatory diseases and obesity have neuroprotective effects [39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…The Immunohistochemistry (IHC) index was determined as the average integral optical density (AIOD), calculated as the positive area multiplied by the optical density, divided by the total area (AIOD = positive area × optical density/total area). The numbers of positive cells were recorded for further analysis, following established protocols [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is revealed that ZA significantly inhibits RANKL/RANK pathway to suppress micrometastasis of cancer. In addition, ZA also reduces the number and persistence of disseminated tumor cells in the bone marrow of patients with breast cancer [ 101 , 102 ], through inhibiting chemokine C-C motif ligand 5 (CCL5)/chemokine receptor (CCR5) and IL-17B/17-BR [ 103 ]. CCL5/CCR5 regulates the coupling of cancer cells and mesenchymal stromal cells [ 104 ], and IL-17B/17-BR stimulates chemokines or enhancing inflammation [ 105 ], both of them facilitate the progression and metastasis of cancer cells.…”
Section: Anticancer Effects Of Zamentioning
confidence: 99%